Aktivitas Mubaligh Syeikh Abdul Manaf Dalam Penyebaran Agama Islam Di Kawasan Bandung Raya Pada Abad Ke 17-18 M - Febri Nugraha (UIN Sunan Gunung Djati Bandung, 2022)
This study examines how the activities of Mubaligh Syeikh Abdul Manaf in the Spread of Islam in the Greater Bandung Area in the 17th-18th Century AD. This research aims to examine the spread of Islam in the Greater Bandung area by Syeikh Abdul Manaf, Mahmud Village, and Cultural Heritage of Syeikh Abdul Manaf. The process of collecting sources was carried out by searching for various books, journals, theses, articles and interviews with key caretakers in Mahmud Village. The method used in this research is to use qualitative methods that are descriptive analysis. Syeikh Abdul Manaf spread his Islam throughout West Java, namely through his students who were scattered to various districts or cities in West Java, for the dissemination carried out by Syeikh Abdul Manaf, namely through various ways, especially through Islamic da'wah. Syeikh Abdul Manaf was the first spreader of Islam in the Bandung Raya area (priangan) in the 17th to 18th century AD. In spreading Islam in the Bandung area and its surroundings, Syeikh Abdul Manaf was assisted by two students, namely Eyang Agung Zaenal Arif and Eyang Abdullah Gedug. It can be concluded, the results of this study indicate that the activities of Syeikh Abdul Manaf in spreading Islam, especially in the Greater Bandung area in the 17-18 century AD were using various methods, especially the Islamic Da'wah method.